Review on authentication mechanisms in cloud computing - Sumathi, D; Jasti, Sireesha (International Journal of Engineering and Technology, 2018)
Cloud computing is one of the most significant revolutionary technologies that provide services from computing infrastructures, applications, and platforms to customers for their personal coalition whenever and wherever needed. Security is considered to be the most important key component in the challenges of cloud computing field. This work discusses about the first level key challenges of security- Authentication. Many authentication schemes have been proposed earlier. But all those schemes work as an entry level for service requisition. When the consumers face any problems during the service availability, then both the consumers and service providers need a quick outlook to the SLA. Based on the severity level of the issue, the service providers need permission to access the service area rented by the consumer. This work provides the critics and reviews of authentication mechanisms that have been carried out earlier. In addition, it also provides an overview of authentication mechanisms carried out by service providers and a comparison of various authentication mechanisms has been discussed.Â Â Â